Feeding Practices of Livestock at Jamalpur Sadar Upazilla in Jamalpur District of Bangladesh - Mahzabin Farzana; Shanaz Alam Sunny; Md Mosharaf Hossain; Mofassara Akter (Research in Agriculture Livestock and Fisheries, 2025)
This study assessed livestock feeding practices, feed resource utilization, and rice straw feeding methods in Jamalpur Sadar Upazila, Bangladesh. A field survey was conducted among 20 small, medium, and large farms using a structured questionnaire. Information on livestock population, feeding systems, milk yield, and animal health was collected through interviews and on-farm observations, and data were analyzed using Microsoft Excel. The livestock composition consisted of 56% cattle, 29% dairy cows, and 14% small ruminants, with crossbred cattle accounting for 64% of the total herd due to their higher milk-producing potential. The average daily milk yield was 6.0 L for crossbred cows and 1.5 L for indigenous cows, contributing to a total daily production of 553 L across the surveyed farms. Commercial feeding systems were practiced by 40% of large farms, whereas small and medium farms predominantly relied on traditional or mixed feeding systems (15% and 45%, respectively). Rice straw was used as a major roughage source in all farms; 80% used unprocessed straw, and 20% used processed forms. Additionally, 45% of farmers practiced grazing, while 55% provided cut-and-carry grass. Unconventional feed resources such as vegetable waste, rice gruel, and fruit peels were also used. The findings indicate that most farmers in Jamalpur Sadar Upazila possess limited knowledge of scientific feeding practices, resulting in predominantly traditional systems that do not meet optimal nutritional requirements. Strengthening farmer training, promoting balanced ration formulation, and encouraging improved straw processing technologies are essential to enhance livestock nutrition and productivity in the region. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 437-447